2016
DOI: 10.20543/mkkp.v32i1.706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vulcanization system and carbon black on mechanical and swelling properties of EPDM blends

Abstract: EPDM (Ethylene propylene diene monomer) is one of synthetic rubber that widely used in automotive. It must be vulcanized and added by other materials before used. The aim of this study is to investigate the effect of vulcanization system and the addition of carbon black (CB) to the mechanical properties and swelling characteristic of EPDM. This research used three vulcanization system: conventional vulcanization (CV), efficient vulcanization (EV), and semi-efficient vulcanization (SEV) with the variation of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…The maximum and minimum torque also decreases with an increased in the temperature. Torque is an amount of force needed to process the blends (Mayasari & Yuniari, 2016), thus, the magnitude of torque needed at a higher temperature is not equal to the one required at a lower temperature. The heat also produces energy that can accelerate a reaction.…”
Section: Results and Discussion Curing Characteristicsmentioning
confidence: 99%
“…The maximum and minimum torque also decreases with an increased in the temperature. Torque is an amount of force needed to process the blends (Mayasari & Yuniari, 2016), thus, the magnitude of torque needed at a higher temperature is not equal to the one required at a lower temperature. The heat also produces energy that can accelerate a reaction.…”
Section: Results and Discussion Curing Characteristicsmentioning
confidence: 99%
“…CV system gives a high crosslink density because it has a high amount of sulfur combined with TMTD accelerator (Dijkhuis et al, 2009) Figure 2 shows that for the overall vulcanization system, the greater carbon black gives the greater crosslink density. It is confirmed that the greater filler loading means the greater delta torque and the greater crosslink density as well (Mayasari & Yuniari, 2016). The degree of cross-linking in filled compounds is greater.…”
Section: Crosslink Densitymentioning
confidence: 60%
“…Meanwhile, EV system gives the lowest crosslink density. In the previous research, it is agreed that EV system gives the lowest delta torque (Mayasari & Yuniari, 2016). In the EV system, the optimum cure time is the fastest than the other systems because EV system contains the lowest sulfur concentration.…”
Section: Crosslink Densitymentioning
confidence: 93%
See 2 more Smart Citations